2011
DOI: 10.1177/0748730410397645
|View full text |Cite
|
Sign up to set email alerts
|

Lab Mice in the Field: Unorthodox Daily Activity and Effects of a Dysfunctional Circadian Clock Allele

Abstract: Daily patterns of animal behavior are potentially of vast functional importance. Fitness benefits have been identified in nature by the association between individual timing and survival or by the fate of individuals after experimental deletion of their circadian pacemaker. The recent advances in unraveling the molecular basis of circadian timing enable new approaches to natural selection on timing. The investigators report on the effect and fate of the mutant Per2 Brdm1 allele in 4 replicate populations of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
100
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 40 publications
4
100
2
Order By: Relevance
“…However, a causal relationship between diurnality and longevity is unlikely here: During the summer, when the long-living mice from the release cohort (the only ones still present from this cohort) became more diurnal, the population density increased. Diurnal behavior under high population densities is consistent with earlier reports of mice maintained under field conditions (14). Activity during the day may have led to a different predation risk between genotypes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, a causal relationship between diurnality and longevity is unlikely here: During the summer, when the long-living mice from the release cohort (the only ones still present from this cohort) became more diurnal, the population density increased. Diurnal behavior under high population densities is consistent with earlier reports of mice maintained under field conditions (14). Activity during the day may have led to a different predation risk between genotypes.…”
Section: Discussionsupporting
confidence: 89%
“…Here, despite laboratory studies showing an array of deleterious physiological consequences for health in Per2 Brdm1 (22), there was no overall effect on fitness in outdoor conditions. In contrast to the tau mutation, the Per2 Brdm1 mutation does not strongly affect the circadian period and had a negligible effect on activity patterns in outdoor conditions (14). We cannot exclude the possibility that the effects we report for the tau mutation may be due to an unknown noncircadian pleiotropic effect, even though the earlier laboratory studies on tau mutant hamsters have clearly revealed health consequences as a result of the deleterious impact of inappropriate entrainment to artificial lighting regimes (17).…”
Section: Discussioncontrasting
confidence: 59%
“…However, recent seminatural studies in mice, hamsters, and Drosophila have revealed some unexpected findings. For example, the widely held belief from laboratory studies that mice and golden hamsters are nocturnal needs to be revised because in the wild they are predominantly or exclusively diurnal (1,2). Similarly in Drosophila melanogaster, locomotor rhythms studied in seminatural conditions reveal that deeply held, laboratory-derived assumptions may require significant revision.…”
mentioning
confidence: 99%
“…Here, we highlight the methods to translate selection experiments into semi-natural conditions using results from two competition experiments with mice [16,87]. The experiments integrated existing monitoring methods with present-day availability of circadian mutants.…”
Section: Case Study 3 Measuring Fitness Consequences Of Circadian Ormentioning
confidence: 99%
“…The mutant and wild-type mice were released into four outdoor enclosures in near Mendelian ratio (homozygote : heterozygote : wild-type ¼ 1 : 2 : 1). However, there was no selection against the mutant allele over the course of two consecutive years [87].…”
Section: Case Study 3 Measuring Fitness Consequences Of Circadian Ormentioning
confidence: 99%